Experience of guselkumab usage in the treatment of patients with psoriatic arthritis in real clinical practice - E. Yu. Loginova; Yu. L. Korsakova; T. V. Korotaeva (Современная ревматология)
The article presents an analysis of literature on the efficacy and safety of a new biologic disease modifying antirheumatic drug usage, the interleukin 23 inhibitor – guselkumab (GUS) – in the treatment of patients with psoriatic arthritis (PsA). Two own clinical observations of GUS therapy are described. It has been demonstrated that in PsA of moderate activity and in severe to moderate psoriasis with nail damage, the use of GUS (100 mg at weeks 0 and 4, and then every 8 weeks), allows to achieve remission of peripheral arthritis, enthesitis and psoriasis by the 20th week of treatment as in the monotherapy regimen and in combination with methotrexate. When GUS is re-prescribed (re-treat) after a long break (10 months), its effectiveness is quickly and completely restored. The safety of GUS was confirmed in patients with comorbid pathology, in particular, Gilbert's syndrome, hyperuricemia, metabolic disorders (abdominal obesity).